Corneal Biomechanics and Refractive Surgery - Guarnieri, Fabio A. (Springer New York : Imprint: Springer, 2015)
This book presents a unique approach not found in any other text for those looking to improve the clinical results of refractive surgery by gaining a better understanding of corneal biomechanics and the instrumentation related to it. Written by leading experts in the field, this book provides authoritative coverage of the interactions of the cornea and the bioinstrumentation, such as corneal topography, pachymetry, aberrometers, tonometry and optical coherence tomography.  Organized in an easy-to-read manner, Corneal Biomechanics and Refractive Surgery is designed for refractive surgeons and general ophthalmologists alike and describes the biomechanical role of the corneal tissue and how each part is affected in refractive surgery. Additionally, showing what the bioinstrumentation can measure, how models can improve understanding of the interaction between biomechanics, bioinstrumentation, and refractive surgery, and how these models and bioinstrumentation together can improve the refractive results, are also discussed.